Manufacture and characterisation of a structural supercapacitor demonstrator - Nguyen,S; Anthony,DB; Katafiasz,T; Qi,G; Razavi,S; Senokos,E; Greenhalgh,ES; Shaffer,MSP; Kucernak,ARJ; Linde,P (Composites Science and Technology, 2024)
Structural power composites, a class of multifunctional materials, may facilitate lightweighting and accelerate widespread electrification of sustainable transportation. In the example considered in this paper, structural power composite fuselage components could provide power to open aircraft doors in an emergency and thus reduce or eliminate the mass and volume needed for supercapacitors currently mounted on the doors. To demonstrate this concept, an 80 cm long multifunctional composite C-section beam was designed and manufactured, which powered the opening and closing of a desktop-scale composite aircraft door. Twelve structural supercapacitor cells were made, each 30 cm × 15 cm × 0.5 mm, and two stacks of four cells were integrated into the web of the beam by interleaving and encasing them with low-temperature-cure woven carbon fibre/epoxy prepreg. This article culminates by considering the engineering challenges that need to be addressed to realise structural power composite components, particularly in an aerospace context.